Analogical Reasoning of Sensing and Intuition Personality Student in Solving Proportion Problem: Two-Variable into Three-Variable Direct Proportion Word Problem - Suwarno, Suwarno; Silvatama, M. Aditiya; Alvarez, Joel I.; Murtafiah, Wasilatul (UNNES JOURNAL, 2024)
Students' analogical reasoning based on sensing and intuition is a topic that has yet to be studied. Specifically, there is a need to explore how these two personalities types process information and apply analogical reasoning to solve proportional problems. The research aims to describe the reasoning process based on students' personalities, especially as a first step in implementing more effective and tailored teaching. The type of research used is descriptive qualitative. The research involved four students, two with sensing personalities and two with intuition personalities, who were selected from a group of 32 seventh grade (A) students at SMP Negeri 3 Ambulu, Jember, Indonesia. Selecting four students allows the researcher to explore how students with sensing and intuition personalities use analogical reasoning. The selected subjects embody both personality types, guaranteeing the consistency and generalizability of the obtained data in a wider context. The triangulation used is a triangulation technique that compares the results of completing analogical reasoning tests and interviews. The results of this study show that students with sensing and intuition personalities show differences in analogical reasoning on proportion material. Sensing students carry out two stages of analogical reasoning, namely encoding and inferring; they identify all the information in the source and target problems, solve the source problem, and recognize material similarities and the context of snack production. However, they needed help at the mapping and applying stages; focusing on concrete details prevented them from seeing abstract relationships, and thus, they failed to use the concept of solving the source problem to the target problem. Meanwhile, intuition students carry out the four stages of analogical reasoning: encoding, inferring, mapping, and applying. They successfully identified information, concluded the source problem, a problem involving two elements, identified the relationship with the target problem, connected the solution steps from the source problem to the target problem, and applied the proportion concept to a more complex target problem. This research shows that students' analogical reasoning in proportion materials varies depending on their personality type. Therefore, we can potentially use the results of this research as a reference to implement differentiated learning. Penalaran analogi siswa berdasarkan kepribadian sensing dan intuition merupakan topik yang belum banyak dikaji secara mendalam. Terutama, bagaimana kedua tipe kepribadian ini memproses informasi dan menerapkan penalaran analogi dalam menyelesaikan masalah perbandingan masih menjadi hal yang kurang dieksplorasi. Penelitian bertujuan untuk mendeskripsikan proses penalaran berdasarkan kepribadian siswa khususnya pada sebagai langkah awal dalam melaksanakan pengajaran yang lebih efektif dan disesuaikan. Jenis penelitian yang digunakan adalah deskriptif kualitatif. Banyak subjek dalam penelitian ini adalah 4 siswa dengan rincian 2 siswa kepribadian sensing dan 2 siswa kepribadian intuition yang dipilih dari 32 siswa kelas VIIA SMP Negeri 3 Ambulu. Jember, Indonesia. Memilih empat siswa memungkinkan peneliti untuk mengeksplorasi secara mendalam bagaimana siswa dengan kepribadian sensing dan intuition menggunakan penalaran analogi. Subjek yang dipilih mewakili kedua tipe kepribadian, sehingga data yang diperoleh konsisten dan dapat digeneralisasi dalam konteks yang lebih luas. Triangulasi yang digunakan adalah triangulasi teknik yang membandingkan hasil penyelesaian tes penalaran analogi dan wawancara. Hasil penelitian ini menunjukkan bahawa siswa dengan kepribadian sensing dan intuition menunjukkan perbedaan dalam penalaran analogi pada materi perbandingan. Siswa sensing melakukan dua tahap penalaran analogi yaitu encoding dan inferring, mereka mengidentifikasi semua informasi dalam masalah sumber dan target serta menyelesaikan masalah sumber dan mengenali persamaan materi serta konteks produksi snack. Namun, mereka kesulitan pada tahap mapping dan applying, fokus pada detail konkret membuat mereka tidak melihat hubungan abstrak sehingga gagal menerapkan konsep penyelesaian masalah sumber ke masalah target. Sementara, siswa intuition melakukan keempat tahapan penalaran analogi: encoding, inferring, mapping, dan applying. Mereka berhasil mengidentifikasi informasi, menyimpulkan masalah sumber yang merupakan masalah perbandingan dua unsur dan mengidentifikasi keterkaitan dengan masalah target, menghubungkan langkah-langkah penyelesaian dari masalah sumber ke target, dan menerapkan konsep perbandingan ke masalah target yang lebih kompleks. Secara keseluruhan, penelitian ini menunjukkan bahwa penalaran analogi siswa dalam materi perbandingan bervariasi tergantung pada tipe kepribadian mereka. Oleh karena itu, hasil penelitian ini berpotensi untuk digunakan sebagai referensi dalam menerapkan pembelajaran berdiferensiasi yang mengakomodasi kebeeragaman tipe kepribadian.